Potential mechanisms of zinc sulfate in inhibiting porcine reproductive and respiratory syndrome virus replication: attenuation of oxidative stress, inflammatory response, and apoptosis - Yang, Huizhen; Zhang, Chengzi; Li, Qianfan; Wu, Zixuan; Sun, Na; Yin, Wei; Fan, Kuohai; Li, Hongquan (Frontiers in Veterinary Science, 2025)
IntroductionThis study aimed to elucidate the mechanism of zinc sulfate against porcine reproductive and respiratory syndrome virus (PRRSV) through transcriptomic data and experimental validation.MethodsInitially, the expression of PRRSV N gene and protein were quantified using qPCR and immunofluorescence, respectively. High-throughput RNA sequencing was performed to analyze global gene expression changes in PRRSV-infected Marc-145 cells treated with zinc sulfate. Transcriptomic data were subjected to bioinformatic analyses, including Venn diagram assessments, protein–protein interaction network construction using the STRING database, and identification of hub genes via Cytoscape 3.10.0. Functional enrichment analysis of Gene Ontology and KEGG pathways were performed using R (v4.4.3). Subsequently, oxidative stress parameters in PRRSV-infected Marc-145 cells treated with zinc sulfate were detected using biochemical assays. The modulatory effects of zinc sulfate on inflammatory response and apoptosis were evaluated through qPCR and western blot, measuring the expression of cytokines (IL-6, IL-8, TNF-α, IL-10), apoptosis-related proteins (Caspase-3, Bax, Bcl-2), and key components of the NF-κB pathway. Finally, flow cytometry was employed to assess cellular apoptosis rates.ResultsThe result demonstrated that zinc sulfate significantly suppressed PRRSV replication. The transcriptomic analysis revealed that compared to the PRRSV-infected group, there were 14 upregulated and 50 downregulated targets in zinc sulfate treatment group. Among these, ten core downregulated and upregulated targets were well enriched in the inflammation and apoptosis pathways, respectively. The experimental verification results demonstrated that compared to the PRRSV-infected group, zinc sulfate treatment significantly diminished intracellular reactive oxygen species (ROS) and malondialdehyde (MDA) levels, while elevating the enzymatic activities of superoxide dismutase (SOD) and catalase (CAT) (p < 0.05). It also suppressed the expression of IL-6, IL-8, TNF-α, while upregulating IL-10 (p < 0.05). In addition to, it also upregulated the phosphorylation levels of IκBα and p65 (p < 0.05), and decreased the expression of Caspase-3, cleaved-Caspase-3, Bax, while enhancing Bcl-2 (p < 0.05). Simultaneously, flow cytometry analysis further confirmed that zinc sulfate substantially attenuated late-stage and overall apoptosis rates in PRRSV-infected cells (p < 0.05).ConclusionThese results implied that zinc sulfate restricted oxidative stress, diminished inflammatory response and induced apoptotic suppression to confer protection against PRRSV infection.